Review: Sporadic Parkinson's disease: development and distribution of α-synuclein pathology - Del Tredici, K.; Braak, H. (Neuropathology and applied neurobiology, 2016)
The development of α‐synuclein immunoreactive aggregates in selectively vulnerable neuronal types of the human central, peripheral, and enteric nervous systems is crucial for the pathogenesis of sporadic Parkinson's disease. The presence of these lesions persists into the end phase of the disease, a process that is not subject to remission. The initial induction of α‐synuclein misfolding and subsequent aggregation probably occurs in the olfactory bulb and/or the enteric nervous system. Each of these sites is exposed to potentially hostile environmental factors. Once formed, the aggregates appear to be capable of propagating trans‐synaptically from nerve cell to nerve cell in a virtually self‐promoting pathological process. A regional distribution pattern of aggregated α‐synuclein emerges that entails the involvement of only a few types of susceptible and axonally interconnected projection neurons within the human nervous system. One major route of disease progression may originate in the enteric nervous system and retrogradely reach the dorsal motor nucleus of the vagal nerve in the lower brainstem. From there, the disease process proceeds chiefly in a caudo‐rostral direction through visceromotor and somatomotor brainstem centres to the midbrain, forebrain, and cerebral cortex. Spinal cord centres may become involved by means of descending projections from involved lower brainstem nuclei as well as by sympathetic projections connecting the enteric nervous system with postganglionic peripheral ganglia and preganglionic nuclei of the spinal cord. The development of experimental cellular and animal models is helping to explain the mechanisms of how abnormal α‐synuclein can undergo aggregation and how transmission along axonal connectivities can occur, thereby encouraging the initiation of potential disease‐modifying therapeutic strategies for sporadic Parkinson's disease.